QUALITATIVE, QUANTITATIVE SCREENING AND ANTIFUNGAL STUDY OF FICUS SEMICORDATA BUCH. -HAM. EX SM - Gandhi, Abhay Jayprakash (International Journal of Public Health Science (IJPHS), 2020)
Objective Ficus semicordata is an ethnomedicinal plant which has a numerous number of medicinal claims and it hasn?t been explored thoroughly. Various parts of plant used medicinally such as used in skin disorder, leprosy, etc.To explore different qualitative, quantitative and antifungal aspect of Ficus semicordata.Materials and methodsDifferent test were carried out to determine qualitative as well as quantitative parameter such as for the presence of protein, glycosides, alkaloids, carbohydrates, terpenoids, etc.Result & DiscussionThe three extracts were taken for examination such as water, methanolic and hydroalcoholic. The study was carried out on Ficus bark, leaves and fruit and for every sample three extract were prepared. And every extract shows different results. Also study revels ficus semicordata shows antifungal activityConclusionThe Ficus semicordata plant extracts could be used as an antifungal after comprehensive in vitro biological studies.